Atrial natriuretic factor stimulates renal dopamine uptake mediated by natriuretic peptide-type A receptor - Fernandez, Belisario Enrique (2005)
To determine the effects of atrial natriuretic factor (ANF) on renal dopamine (DA) metabolism, 3H-DA and 3H-L-DOPA uptake by renal tubular cells was measured in experiments carried out in vitro in Sprague-Dawley rats. The receptor type involved was also analyzed. The results indicate that ANF increased at 30 min, DA uptake in a concentration-response fashion having 10 pM ANF as the threshold concentration. Conversely, the uptake of the precursor L-DOPA was not modified by the peptide. ANF effects were observed in tissues from external and juxtamedullar cortex and inner medulla. On this basis, 100 nM ANF was used to continue the studies in external cortex tissues. DA uptake was characterized as extraneuronal uptake, since 100 microM hydrocortisone blocked ANF-induced increase of DA uptake. Renal DA uptake was decreased at 0 degrees C and in sodium-free medium. The effects of ANF in these conditions were not present, confirming that renal DA uptake is mediated by temperature- and sodium-dependent transporters and that the peptide requires the presence of the ion to exhibit its actions on DA uptake. The biological natriuretic peptide type A receptor (NPR-A) mediates ANF effects, since 100 nM anantin, a specific blocker, reversed ANF-dependent increase of DA uptake. The natriuretic peptide type C receptor (NPR-C) is not involved, since the specific analogous 100 nM 4-23 ANF amide has no effect on renal DA uptake and does not alter the effects of 100 nM ANF. In conclusion, ANF stimulates DA uptake by kidney tubular cells. ANF effects are mediated by NPR-A receptors coupled to guanylate cyclase and cGMP as second messenger. The process involved was characterized as a typical extraneuronal uptake, and characterized as temperature- and sodium-dependent. This mechanism could be related to DA effects on sodium reabsorption and linked to ANF enhanced natriuresis in the kidney. The increment of endogenous DA into tubular cells, as a consequence of increased DA uptake, would permit D1 receptor recruitment and Na+,K+-ATPase activity inhibition, which results in decreased sodium reabsorption and increased natriuresis.